2015
DOI: 10.1159/000431176
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Yellow, Red, and Infrared Laser and LED Stimulation: Changes of Vascular Parameters in a Chick Embryo Model

Abstract: Background: The use of transcranial laser or light-emitting diode (LED) therapy in the treatment of different neurological diseases is attracting increasing attention. The main goal of this study was to investigate different kinds of scientifically and commercially available laser (yellow, red, and infrared) and LED stimulation systems for the first time using a chick embryo model under a fixed human cadaver (scalp and/or skull) and without this anatomical preparation. Methods: In the present study, the extra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Based on the investigation of the peer‐reviewed literatures on the wavelength selection for transcranial LLLT , we found that there were mainly four wavelengths used in LLLT community, no matter the research or clinical field. Litscher recently extended mice experimental study to human skull and scalp‐skull‐chick embryo head model study on the wavelength selection, however, human cerebral tissue and cerebrospinal fluid was still unconcerned . Therefore, there was no study on the whole human head to address the issue about the optimal selection on all candidate wavelengths in LLLT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the investigation of the peer‐reviewed literatures on the wavelength selection for transcranial LLLT , we found that there were mainly four wavelengths used in LLLT community, no matter the research or clinical field. Litscher recently extended mice experimental study to human skull and scalp‐skull‐chick embryo head model study on the wavelength selection, however, human cerebral tissue and cerebrospinal fluid was still unconcerned . Therefore, there was no study on the whole human head to address the issue about the optimal selection on all candidate wavelengths in LLLT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we are looking forward to perform the neurobehavioral test on 1064 nm photon transcranial stimulation, and test if 1064 nm acted the same with 980 nm at the initial stage. Then, other wavelengths (eg, 589 nm as suggested in Litscher's newly studies ) and other illumination parameters are expected to get both the quantitative photon penetration analysis and neurobehavioral performance evaluation results in transcranial LLLT experimental study. After further and fully testing this hypothesis, it is not hard to foresee the online and precise optimization of LLLT illumination parameters with this resource‐saving, time‐saving, quantitative and 3D visible method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prototype system is currently based on infrared lasers using a wavelength of 810 nm. This wavelength has recently been proven (July 2018) to be one of the best for transcranial laser stimulation [ 4 , 5 ]. The authors employed Monte Carlo modeling and a visible human phantom to compute the penetrated photon fluence distribution within the cerebral cortex.…”
mentioning
confidence: 99%
“…Gerhard Litscher from Medical University of Graz and comprises many partners from China. In the following, some milestones and publications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] from the year 2015 are listed chronologically:…”
mentioning
confidence: 99%